Anthocyanins from Hibiscus syriacus L. Inhibit NLRP3 Inflammasome in BV2 Microglia Cells by Alleviating NF-κB- and ER Stress-Induced Ca(2+) Accumulation and Mitochondrial ROS Production - Molagoda, Ilandarage Menu Neelaka (Oxid Med Cell Longev, 2021)
Anthocyanins from the petals of Hibiscus syriacus L. (PS) possess anti-inflammatory, antioxidant, and antimelanogenic activities. However, it remains unclear whether PS inhibit the NLR family pyrin domain-containing 3 (NLRP3) inflammasome activation and assembly. This study is aimed at investigating whether PS downregulate NLRP3-mediated inflammasome by inhibiting nuclear factor-κB (NF-κB) and endoplasmic reticulum (ER) stress. BV2 microglia cells were treated with PS in the presence of lipopolysaccharide and adenosine triphosphate (LPS/ATP), and the NLRP3-related signaling pathway was investigated. In this study, we found that LPS/ATP treatment activated the NLRP3 inflammasome, which resulted in the release of interleukin-1β (IL-1β) and IL-18. Meanwhile, PS reduced LPS/ATP-mediated NLRP3 inflammasome at 12 h by inhibiting ER stress-mediated Ca(2+) accumulation and subsequent mitochondrial reactive oxygen species (mtROS) production, which, in turn, decreased IL-1β and IL-18 release. Furthermore, PS inhibited the NLRP3 inflammasome 1 h after LPS/ATP treatment by suppressing the NF-κB pathway, which downregulated Ca(2+) accumulation and mtROS production. These data showed that PS negatively regulated activation of the NLRP3 inflammasome in a time-different manner by inhibiting the NF-κB signaling pathway in the early stage and the ER stress response in the late stage. The pathways shared Ca(2+) accumulation-mediated mtROS production, which was significantly inhibited in the presence of PS. In conclusion, our results suggested that PS has potential as a supplement against NLRP3 inflammasome-related inflammatory disorders; nevertheless, further studies are needed to determine the effect of PS in the noncanonical NLRP3 inflammasome pathways and pathological conditions in vivo.